UPAYA MENINGKATKAN KEPERCAYAAN DIRI MELALUI LAYANAN BIMBINGAN KELOMPOK - Rian, Rian; Astuti, Indri; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractOn of the keys to a personâ€™s success in living daily life whether it is in a school environment or in an outdoor setting that involves having confidence. Confidence is a positive attitude of an individual who enables himself to develop positive value both for himself and for the environment or situation he or she faces. A common problem with this research: â€œHow is the improvement of learners confidence through group guidance services to the class X IPA 1 High school country 3 Pontianak. While sub problems are that: (1) how is the self-confidence of a learner before it is given group guidance service to the class X IPA 1 High School Country 3 Pontianak, (2) how is the group guidance service planning stage to increase learnersâ€™ confidence in the class X IPA 1 High school country 3 Pontianak, (3) how is the conduct of the group guidance service to increase learners, confidence in the class X IPA 1 High school country 3 Pontianak, (4) how is confidence enhanced after being given group guidance service to class learners X IPA 1 High school country 3 Pontianak. The variables in this study consist of problem variables: self confidence, Act variable: group guidance, The subject of research is as much as 7 public high school learners 3 pontichild with low self-confidence with an indicator (1) confidence in ability, (2) optimist, (3) objective, (4) be responsible (5) rational and realistic. The method used is a descriptive method and form of the research is a study of counseling action. Data collection techniques with questionnaire, observation, interview, whereas data analysis techniques use a percentage formula, planning and implement group guidance format, T-Test formula. Based on research on the subjectâ€™s self confidence after action by group guidance, it reached 83% in the â€œhighestâ€ category.Â Keywords: Group Guidance, Increase Self ConfidenceÂ